2010
DOI: 10.1074/jbc.m109.079962
|View full text |Cite
|
Sign up to set email alerts
|

Foxo1, a Novel Regulator of Osteoblast Differentiation and Skeletogenesis

Abstract: Skeletogenesis depends on the activity of bone-forming cells derived from mesenchymal cells. The pathways that control mesenchymal cell differentiation are not well understood. We propose that Foxo1 is an early molecular regulator during mesenchymal cell differentiation into osteoblasts. In mouse embryos, Foxo1 expression is higher in skeletal tissues, while Foxo1 silencing has a drastic impact on skeletogenesis and craniofacial development, specially affecting pre-maxilla, nasal bone, mandible, tibia, and cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
120
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(132 citation statements)
references
References 56 publications
12
120
0
Order By: Relevance
“…The expression of FoxO1 was increased during osteoblast differentiation. (30) miR-182, a negative regulator of FoxO1, was also increased along with osteogenesis in the present study and we speculated that it might be a feedback response to prevent further increases in expression of the target gene.…”
Section: Foxo1 Is a Target Of Mir-182 In C3h10t1/2 Mesenchymal Stem Cmentioning
confidence: 64%
See 3 more Smart Citations
“…The expression of FoxO1 was increased during osteoblast differentiation. (30) miR-182, a negative regulator of FoxO1, was also increased along with osteogenesis in the present study and we speculated that it might be a feedback response to prevent further increases in expression of the target gene.…”
Section: Foxo1 Is a Target Of Mir-182 In C3h10t1/2 Mesenchymal Stem Cmentioning
confidence: 64%
“…First, FoxO1 inhibited apoptosis and promoted differentiation of osteoblast lineage cells, in direct contrast to the effects of miR-182 overexpression in osteo-lineage cells. (8,9,30) The expression of Runx2 and Osterix has also been shown to be suppressed in FoxO1 knockout mice. (8,9) Second, miR-182 has been demonstrated to regulate FoxO1 in a breast cancer cell line.…”
Section: In Vivo Effect Of Mir-182 In Bone In a Zebrafish Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression of Runx2 is controlled by Foxo1 which can also directly interact with this transcription factors. Teixeira and coworkers suggested that Foxo1 is an early molecular regulator during mesenchymal cell differentiation into osteoblast exerting its effects through regulation and interaction with Runx2 (Teixeira et al, 2010). Several studies have indicated that Runx2 is a context-dependent transcriptional activator and repressor and may interact with other regulatory proteins, suggesting a complex mechanism of osteoblastogenesis control by this factor.…”
Section: Runx2 (Runt-related Transcription Factor 2)mentioning
confidence: 99%